PENGARUH FIRM SIZE, LIQUIDITY, LEVERAGE, PROFITABILITY, DAN GROWTH TERHADAP DIVIDEND POLICY - Jessica Jecia; Sufiyati Sufiyati (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to examine the effect of firm size, liquidity, leverage, profitability, and growth on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used was purposive sampling. The sample in this study were 39 companies. This study uses multiple linear regression analysis using Eviews 12 software. The results of this study indicate that liquidity and growth have a negative and significant effect on dividend policy. While other variables, namely firm size, leverage, and profitability have a positive and insignificant effect on dividend policy.